DEVELOPING WORD SEARCH MAKER AS MEDIA IN WRITING RECOUNT TEXT FOR EIGHTH GRADE STUDENTS AT SMP SWASTA YPI DHARMA BUDI SIDAMANIK - Khairunnisa Tambunan; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The study was aimed to develop media based on Word Search Maker in teaching writing recount text for grade VIII students in SMP Swasta YPI Dharma Budi Sidamanik. This study was conducted by using Research and Development (R&D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of the study was Grade VIII of SMP Swasta YPI Dharma Budi Sidamanik. The data were gathered by administering interview to English teacher and distributing questionnaire to 30 respondents to get the students’ needs. The interview and questionnaire result prove that the students’ needs English learning media which can motivate the students to understand about the recount writing. The product has been validated by experts. The result of the product was word puzzle game to be used in mastering the recount text writing. The result of experts’ validation showed that the media was an appropriate media to be used in teaching writing recount text by getting the average percentage of 85,2% categorized as very good.